Financial Sector Assessment Program - Poland : Housing Finance Technical Note - World Bank (Washington, DC, 2014)
This note primarily addresses the mortgage market development objectives, although the regulator is encouraged to consider the use of the macro prudential tools at its disposal for institutional and systemic stability of the mortgage sector as the current portfolio outstanding is large and risky and thus presents a negative performance outlook. The rest of the material is structured as follows. Firstly, brief background information on recent Polish mortgage sector evolution provides context. Secondly, details of certain regulatory initiatives are discussed with the view on potential strengthening. Thirdly, suggestions for modernization of certain features of the current capital market funding framework are provided; specifically on expanding the issuance of Mortgage Covered Bond (MCBs) to the universal banks as well as bringing the framework in line with the latest global best practices.